PEMBANGUNAN POLITIK DAN TEORITIS - Harun Umar (Universitas Nasional, 2020)
One of the developments in political science is the emergence of political development studies as a separate field of study, in addition to other fields of study such as political theories, political institutions, parties, groups and public opinion, and international relations. Western scholars develop this study in their efforts to understand the socio-political changes in developing countries. Therefore, the context of political development tends to be aimed at developing countries with the assumption that rationalization, integration and democratization have not yet been implemented in these countries.